Bilateral Symmetry of Distortions of Tactile Size Perception. (November 2015) - Longo, Matthew R.; Ghosh, Arko; Yahya, Tasneem
The perceived distance between touches on the limbs is generally bigger for distances oriented across the width of the limb than for distances oriented along the length of the limb. The present study aimed to investigate the coherence of such distortions of tactile size perception across different skin surfaces. We investigated distortions of tactile size perception on the dorsal and palmar surfaces of both the left and right hands as well as the forehead. Participants judged which of two tactile distances felt larger. One distance was aligned with the proximodistal axis ( along the body), the other with the mediolateral axis ( across the body). Clear distortions were found on all five skin surfaces, with stimuli oriented across the width of the body being perceived as farther apart than those oriented along the length of the body. Consistent with previous results, distortions were smaller on the palmar than on the dorsal hand surface. Distortion on the forehead was intermediate between the dorsal and palmar surfaces. There were clear correlations between distortion on the left and right hands, for both the dorsal and palmar skin surfaces. In contrast, within each hand, there was no significant correlation between the two skin surfaces. Distortion on the forehead was not significantly correlated with that on any of the other skin surfaces. These results provide evidence for bilaterally symmetric representations underlying tactile size perception.